HUBUNGAN PENDIDIKAN JASMANI TERHADAP PEMBENTUKAN KARAKTER SISWA KELAS IV SD NEGERI 050707 TELAGA JERNIH - Anggie Puspita Sari Nasution; Winara; Khairul Usman; Fajar Sidik Siregar; Try Wahyu Purnomo (STKIP Subang, 2025)
This study aims to determine the relationship between physical education and character building of students. The study was conducted at SD Negeri 050707 Telaga Jernih. The sample in the study were all 36 fourth grade students (IVA and IVB). The research method used was a quantitative approach with a correlational design. Data collection techniques were carried out through interviews, observations, and distribution of closed questionnaires based on a Likert scale consisting of 30 statements. Data analysis was carried out through instrument validity and reliability tests, normality tests, and Spearman's rho correlation tests because the data were not normally distributed. The results showed that the research instrument was declared valid and reliable, with a Cronbach's Alpha value > 0.70. The normality test produced a significance of <0.05, so the data were not normal and were analyzed using Spearman's rho. The correlation results showed a coefficient value of 0.418 with a significance of 0.011 (<0.05), which means there is a positive and significant relationship between physical education and character building of students. Thus, this study is the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. This confirms that the better the implementation of physical education, the better the character development of students, particularly in the areas of honesty, discipline, responsibility, sportsmanship, and tolerance. Therefore, physical education plays a crucial role not only in developing physical skills but also in developing positive character in elementary school students.